PENGEMBANGAN ‘MARINE BUSINESS’ DI WILAYAH PESISIR TIMUR SUMATERA UTARA - Muchtar Ahmad (DINAMIKA PERTANIAN, 2016)
In developing of the eastern coastal zone in the North Sumatra province, emerged various ideas from rural coastal development in 1974, fishery metropolis in 2005, fishery industrialization until blue economy popularize as sustainable development in the fishery and marine businesses recently. However, at the national wise, the fisheries development is still dependent on productivity increasing, growth and investment policy. Although no evaluation on those ideas and policies implementation have been conducted and published. The issue of poverty, unbalance growth, inequality, and low capital investment together with environmental degradation in the coastal area have not yet shift to the due hope; even become down into worse situation. Therefore, base on economic geography the idea of development pattern called marine business system in the region is arranged. It is one of might be effective alternatives to address the issues in microeconomic sense. The idea is base on the assumption that the coastal area, indeed still open the opportunity to utilize for social wellbeing. Unfortunately it would not be persistence with the present strategy as ever. Developing marine business system need good governance together with best practices as moral hazard become worsen, so that the law enforcement is a must to be successful.